EGGS AND EARLY LARVAE OF THE GREY MULLET VALAMUGIL SEHELI (FORSSKAL) - Bensam, P (Indian Journal of Fisheries, 2011)
Planktonic eggs coUoplcd from P^k.Bsy ,ancl Gulf of Mannar and identifiedcirciunstantially as of Valamugil seheli (Forsskal) were reared in the laboratoryup to the 72-h postlarvae. The eggs ranged in diameter from 0.621 mm to 1.09mm and were with single, pigmented oilglobules ranging in diameter from 0.212mm to 0.273 mm. The periviteUine space was narrow. The yolk, being neithersagmented nor vacuolated, was clear. Newly hatched larvae measured 2.179mm.They had black pigment spots on the dorsal side of the body, with a few localised,yellowish networks of xanthophores. In the 24-h larva, most of the black pigmentspots had migrated to the ventral side of the body. The 48-h-old larva had itsmouth formed, eyes pigmented, yolk utilized and pectoral fins developed, and sowas in the early postlarval stage. In the 72-h larva there was iiicrease in pigmentationalong both dorsal and ventral aspects of body. In this postlarval phasethe number of myomeres had stabilized at 25, corresponding to the adult-vertebralnumber.